3D-printed immersion micro optics - Marco Wende; Kathrin Doth; Michael Heymann; Andrea Toulouse (Light: Advanced Manufacturing)
Femtosecond 3D-printing offers tantalizing avenues for miniaturization and integration of micro optical systems. Available photoresists, however, restrain their utility in liquid immersion, especially in media with refractive indices larger than n = 1.33, such as glues or biomedical fluids. We present monolithic 3D-printed immersion optics, equipped with compact microfluidic sealing to protect the micro optical device from intrusion of liquid immersion media. We experimentally demonstrate diffraction limited performance in water, silicone-, and immersion oil, for a tailored aspherical-spherical doublet with a numerical aperture of NA = 0.625 and a footprint as small as a single mode optical fiber. Such compact monolithic immersion micro optics yield high potential to advance miniaturization for in situ biomedical sensing and robust coupling between fibers and photonic integrated circuits.